Esophageal stricture in lichen planus - Jemshad Alungal; Mansoor C. Abdulla; Rooby Shaheer; Ram Narayan (Journal of Digestive Endoscopy, 2016)
Lichen planus (LP) is a rare cause of esophageal stricture. It is usually associated with oral mucosal involvement, and the diagnosis has to be considered in these patients who present with dysphagia. We present a case of esophageal stricture secondary to LP.